Design, Practice, And Anxiety Reduction: A Meta-Analysis Of STEM-Oriented Interventions for Preservice Primary Teachers’ Foreign Language Speaking Confidence - Dr. Sofia M. Kallström; Dr. Mehmet A. Yılmaz (European International Journal of Pedagogics, 2026)
Foreign language speaking anxiety remains a persistent barrier to oral performance, participation, and communicative development across second and foreign language settings, with consequences that extend from learners’ moment-to-moment classroom engagement to their long-term willingness to use the target language in professional contexts (Ansari, 2015; Bailey, 2020; Bashori et al., 2022). For preservice primary teachers, the stakes are amplified: they are expected to model communication, facilitate interaction, and create emotionally safe learning environments, yet many teacher candidates report anxiety when speaking in a foreign language and uncertainty about how to design learning tasks that support confident oral production. In parallel, teacher education has intensified attention to STEM-oriented design practices, which promote iterative problem-solving, collaboration, and authentic communication—conditions that may indirectly reshape affective barriers and strengthen self-efficacy beliefs related to performance (Bandura, 1997; Aslan-Tutak et al., 2017; DiFrancesca et al., 2014). This article develops a publication-ready meta-analytic synthesis focused on intervention studies that address speaking anxiety and speaking performance, while theoretically integrating mechanisms from STEM design-based teacher education and self-efficacy theory. Using established meta-analysis principles and methodological guidance, the study constructs an interpretive quantitative-qualitative synthesis pathway: defining eligibility boundaries, coding intervention characteristics, and interpreting patterns of effects and heterogeneity through a mechanism-focused lens (Arthur Jr. et al., 2001; Desimone, 2009; Bangert-Drowns et al., 2004). The results are presented as a descriptive meta-analytic narrative that traces how particular intervention logics—flipped learning, web-based speaking practice, remote tasks, gamified language learning, voice-based interaction, dynamic assessment, and embodied methods—operate as anxiety-reduction pathways, and how STEM-oriented design practice in preservice preparation may amplify those pathways by providing mastery experiences, peer collaboration, and professional identity development (Abdullah et al., 2021; Abuhussein et al., 2023; Ali, 2022; Anton, 2009; Blackmore et al., 2018). The discussion advances a practical framework for designing preservice programs that deliberately connect STEM design pedagogy and language speaking interventions to reduce anxiety and strengthen speaking confidence, while acknowledging limitations of evidence transfer across populations and the methodological constraints typical of intervention research (Desimone, 2009; Becker & Park, 2011).